Enhancement of the helical content and stability induced in a linear oligopeptide by an i, i+4 intramolecularly double stapled, overlapping, bicyclic [31, 22, 5]‐(E)ene motif. Issue 1 (January 2014) - Mazzier, Daniela; Peggion, Cristina; Toniolo, Claudio; Moretto, Alessandro
ABSTRACT Two consecutive i, i+4 intramolecular, side chain‐to‐side chain, macrocyclizations of different type carried out on a preformed, partially helical peptide result in a largely predominant, double stapled, overlapping, bicyclic [31, 22, 5]‐(E)ene motif. A detailed ECD and NMR conformational study revealed a significant enhancement of the original helical content and stability, accompanied by an increase of the α‐helix amount over that of the 310‐helix. © 2013 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 102: 115–123, 2014.